2015
DOI: 10.1038/srep14082
|View full text |Cite
|
Sign up to set email alerts
|

Genomic insights into the taxonomic status of the Bacillus cereus group

Abstract: The identification and phylogenetic relationships of bacteria within the Bacillus cereus group are controversial. This study aimed at determining the taxonomic affiliations of these strains using the whole-genome sequence-based Genome BLAST Distance Phylogeny (GBDP) approach. The GBDP analysis clearly separated 224 strains into 30 clusters, representing eleven known, partially merged species and accordingly 19–20 putative novel species. Additionally, 16S rRNA gene analysis, a novel variant of multi-locus seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
275
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(298 citation statements)
references
References 60 publications
19
275
0
4
Order By: Relevance
“…The three species Bacillus anthracis (the causative agent of anthrax), Bacillus cereus, and Bacillus thuringiensis are well over 99% identical and should all be designated as a single species (Helgason et al, 2000), although their names have not been changed despite their near-identity revealed by sequencing. As a compromise, taxonomists created the category Bacillus cereus group, between the level of species and genus, to include these three species and at least five others (Liu et al, 2015), all of which are extremely similar to one another. In some cases, two organisms that should be called the same species may even have different genus names.…”
Section: Ambiguity Among Microbial Species and Strainsmentioning
confidence: 99%
“…The three species Bacillus anthracis (the causative agent of anthrax), Bacillus cereus, and Bacillus thuringiensis are well over 99% identical and should all be designated as a single species (Helgason et al, 2000), although their names have not been changed despite their near-identity revealed by sequencing. As a compromise, taxonomists created the category Bacillus cereus group, between the level of species and genus, to include these three species and at least five others (Liu et al, 2015), all of which are extremely similar to one another. In some cases, two organisms that should be called the same species may even have different genus names.…”
Section: Ambiguity Among Microbial Species and Strainsmentioning
confidence: 99%
“…Within Borrelia burgdorferisensu stricto, the North American Lyme disease spirochete, some sequence clusters are associated with different rodent species (101,162), although it is not yet clear whether the adaptations to specific hosts are genome-wide adaptations or are due primarily to a single outer-surface protein (163). In some cases, host specificity is determined by plasmids, and the bacteria can adapt from one host species to another with acquisition of plasmids, as seen in legume-infecting Rhizobium ecotypes (133) or mammal-versus insect-infecting ecotypes in B. cereus sensu lato (143).…”
Section: Resource Differences Among Pathogensmentioning
confidence: 99%
“…In summary, we can hypothesize that the most easily reversible ecological divergences will involve acquisitions and losses of plasmids that circulate through a given taxon, as seen in R. leguminosarum (133), E. coli (131), and B. cereus (143). Perhaps next easiest is acquisition of an adaptation through homologous recombination, as in the case of antibiotic resistance in Neisseria (135), although even a single gene can create ameliorative evolution (139,142).…”
Section: The Genetic Basis Of Early Diversificationmentioning
confidence: 99%
“…This generally implies the application of large populations of the microorganism of interest with the aim of promoting its establishment and colonization. However, this practice may cause disturbances in the microbial communities of the agro-systems (Trabelsi et al, 2013), particularly when inoculating biological control agents, since their biological activity is not specific or selective for the phytopathogenic agent in question, which may cause unpredictable changes in the microbial (Hoffmaster et al, 2006;Liu et al, 2015). Recientemente, estudios comparativos con genomas completos mediante dDDH (digital DNA: DNA hybridization), evidenciaron la amplia distribución de genes cry y plásmidos tipo pXO en miembros de este grupo, demostrando la baja correlación que existe entre posición filogenética y la presencia o ausencia de estos plásmidos (Liu et al, 2015).…”
Section: Discusión Y Perspectivas De Bioseguridad Y Biodiversidad En mentioning
confidence: 99%
“…However, in widely related species such as B. cereus, B. anthracis and B. thuringiensis, the differentiation using virulence factors and contents of plasmids is limited, due to its loss and transference during the evolutionary history of these species (Hoffmaster et al, 2006;Liu et al, 2015). Recent comparative studies with complete genomes using dDDH (digital DNA: DNA hybridization) showed the distribution of cry genes and type pXO plasmids in members of this group, showing the low correlation between the phylogenetic position and the presence or absence of these plasmids (Liu et al, 2015). The above study also showed the low resolution of the multilocus sequence typing (MLST) for the differentiation at the level of species.…”
Section: Discusión Y Perspectivas De Bioseguridad Y Biodiversidad En mentioning
confidence: 99%